Implementasi Game Hangman Multiplayer Menggunakan Socket dan Multithreading Berbasis Protokol TCP - Marieska, Mastura Diana (AI Society & STMIK Indonesia, 2024)
Multiplayer games tend to be more engaging and can offer a more enjoyable experience compared to single-player games. Hangman, a word-guessing game, is commonly played in groups. When players are in different locations, a reliable connection mechanism is crucial to maintain uninterrupted gameplay. In this study, the Hangman game was implemented using socket programming and multithreading. Sockets were used as the connection mechanism between the players and the server. TCP protocol, which is reliable, was used in this implementation to maintain integrity of communication between clients and server. To allow multi players to participate simultaneously, multithreading was implemented. On the server side, each connected client was assigned a dedicated thread, allowing independent and parellel communication between server and each client. Blackbox testing result indicate that all features of the Hangman game were succesfully implemented and functioned properly.